Barriers and facilitators to implementing the Carer Support Needs Assessment Tool in a community palliative care setting. (2nd June 2019) - Horseman, Zoe; Milton, Libby; Finucane, Anne
ABSTRACT: Family carers play a central role in community-based palliative care. However, caring for a terminally ill person puts the carer at increased risk of physical and mental morbidity. The Carer Support Needs Assessment Tool (CSNAT) enables comprehensive assessment of carer support needs. The present study aimed to identify barriers and facilitators to implementing the CSNAT in a community specialist palliative care service. Semi-structured interviews with 12 palliative care nurse specialists from two community nursing teams in Lothian, Scotland, June 2017. Data was audio-recorded, transcribed and analysed. Palliative care nurse specialists acknowledge the importance of carers in palliative care and encourage carer support practices. Nurses perceived the CSNAT as useful, but used it as an 'add-on' to current practice, rather than as a new approach to carer-led assessment. Further training is recommended to ensure community palliative care nurses are familiar with the broader CSNAT approach.